Changes of electrocardiograms and heart morphology of animals with different resistance to hypoxia under influences of stress - Denefil, О.; Pelykh, V. (Quality in Sport, 2023)
Stress is a process that increases a person’s adaptive capacity and leads to the various diseases, such as hypertension, coronary artery disease, heart attack, cardiac arrest, stroke, mental disorders such as depression and anxiety and even sudden death. Individual response to stress may depend on age, gender, features of autonomic regulation, state of the central nervous system, endocrine systems, higher nervous activity. With excessive stress, the work of internal organs is disturbed, in particular, the cardiovascular system. Determination of the damaging effect of stress on the cardiovascular system in individuals with different reactivity will contribute to the development of individual correction methods. The aim of the study was to analyze the changes in electrocardiograms (ECG) and morphological feachers after stress in animals with different resistance to hypoxia. Material and methods of investigation. Experiments were performed on 48 Wistar rats, with high and low resistance to hypoxia (HRH, LRH), aged 5–6 months. Animals were divided into two groups – control and experimental (after immobilization stress). Individuals with different resistance to hypoxia were selected by method of V. Ya. Berezovsky. Stress was modeled by three one-hour immobilization of rats, which were immobilized on their backs with an interval of 24 hours between each stressful episode. Investigation we did after 24 hours after third immobilization. Under anesthesia were registrated ECG and taken heart for morphological investigation. Sections were stained with hematoxylin and eosin. Results. In examining the ECG in control HRH and LRH animals, no significant difference in the analyzed ECG indicators was established. 24 hours after the last 1 hour three-time immobilization in HRH rats were noted an increase in heart rate, a decrease of the duration of the RR interval, a decrease of the amplitude of the R wave, an increase of QTc interval, an increase of the amplitude of the T wave, an increase in the deviation of the ST segment from the isoline. In LRH rats, stress caused an increase in heart rate, a decrease in the duration of the RR interval, a decrease in the duration of the PQ interval, a decrease in the amplitude of the R wave, an increase in the amplitude of the T wave, an increase in the deviation of the ST segment from the isoline. When comparing the parameters of НRH and LRH rats, in LRH were found a smaller amplitude of the P wave, a smaller amplitude of the R wave, a smaller value of the QTc interval, greater deviation of the ST segment from the isoline. Physiological changes on ECG can also connected with morphological feaches. Conclusions. Stress leads to changes in functional and histological properties of heart, which depends on resistance to hypoxia. In the ECG 24 hours after the last 1 hour three-time immobilization in HRH and LRH rats were noted an increase in heart rate, a decrease of the duration of the RR interval, a decrease of the amplitude of the R wave, an increase of the amplitude of the T wave, an increase in the deviation of the ST segment from the isoline. In HRH rats were also an increase of QTc interval, in LRH rats – a decrease in the duration of the PQ interval. Indxes changes were grater in LRH rats. Mophological changes was higher also in LRH animals.